2009
DOI: 10.1007/s11144-009-0020-6
|View full text |Cite
|
Sign up to set email alerts
|

Dechlorination of p-nitrochlorobenzene using fly ash. Effects of metals, mixed solvents and temperature

Abstract: An efficient method for the dechlorination of p-nitrochlorobenzene on fly ash was developed. Reaction conditions were optimized and higher dechlorination (75%) was achieved at 60°C in water/isopropanol mixture. Metal contents of fly ash played a vital role in enhancing dechlorination. Moreover, the fly ash particles provided the surface to accomplish reduction and substitution reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…55 mS/cm; TDS 963 mg⋅dm −3 ; nitrates 57 ppm and the dissolved salt contents salinity was 0.1 ng⋅dm −3 . The sample was preserved and filtered as described in earlier studies [11][12][13][14]. The filtered sample was analysed on GC-ECD for lindane using internal standard technique as described by Zinovyev et al [19].…”
Section: Dechlorination Of Lindane Present In Industrialmentioning
confidence: 99%
See 2 more Smart Citations
“…55 mS/cm; TDS 963 mg⋅dm −3 ; nitrates 57 ppm and the dissolved salt contents salinity was 0.1 ng⋅dm −3 . The sample was preserved and filtered as described in earlier studies [11][12][13][14]. The filtered sample was analysed on GC-ECD for lindane using internal standard technique as described by Zinovyev et al [19].…”
Section: Dechlorination Of Lindane Present In Industrialmentioning
confidence: 99%
“…In our previous studies we used fly ash, activated carbon, and reducing media to achieve hydrodechlorination. Dechlorination of chlorobenzene compounds was achieved by applying alkaline solutions and sulfur in aqueous/organic solvent [11][12][13][14]. We applied Devarda's alloy and NaBH 4 for dechlorination of DDT and TCP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that presence of sulfur, alkali solution, organic, and aqueous media was important to dechlorinate the chlorinated compounds (31). In present studies, research was focused to enhance the dechlorination (%) of di-chlorobenzene and tri-chlorobenzene compounds by using various alkali solutions under mild conditions.…”
Section: Introductionmentioning
confidence: 99%